2004
DOI: 10.2165/00019053-200422040-00002
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Self-Report Instruments Measuring Health-Related Work Productivity

Abstract: Health impairment often leads to work impairment in the form of both absenteeism and presenteeism (i.e. reduced productivity while at work). Several self-report productivity instruments have been designed over the past few years to measure the impact of illness on productivity at work and/or in non-work activities. In a review of the literature we identified six generic subjective instruments - the Endicott Work Productivity Scale, Health and Labor Questionnaire, Health and Work Questionnaire, Health and Work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
230
0
14

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(246 citation statements)
references
References 36 publications
2
230
0
14
Order By: Relevance
“…8 In a 2004 review of 6 self-reported productivity loss instruments, the WLQ was one of 2 instruments reported to offer a significant advantage over others as a result of extensive testing and the ability to measure general health impact and impact of specific conditions. 9 Research has shown that the WLQ has relatively strong validity and reliability, has been used in a variety of workplace settings with a variety of health risks and conditions, and may be most useful in general employee populations. 10 Productivity loss related to presenteeism was measured with the question: ''In the past 2 weeks, how much of the time did your physical health or emotional problems make it difficult for you to do the following?''…”
Section: Population Health Managementmentioning
confidence: 99%
“…8 In a 2004 review of 6 self-reported productivity loss instruments, the WLQ was one of 2 instruments reported to offer a significant advantage over others as a result of extensive testing and the ability to measure general health impact and impact of specific conditions. 9 Research has shown that the WLQ has relatively strong validity and reliability, has been used in a variety of workplace settings with a variety of health risks and conditions, and may be most useful in general employee populations. 10 Productivity loss related to presenteeism was measured with the question: ''In the past 2 weeks, how much of the time did your physical health or emotional problems make it difficult for you to do the following?''…”
Section: Population Health Managementmentioning
confidence: 99%
“…Indirect attempts have included creating proxy measures from existing symptom and quality-of-life questionnaires (5) and defining it as simply the absence of sick leave in persons with health conditions (6,7). Measures that assess presenteeism directly are of interest here; their descriptions and psychometric properties are available in 2 recent reviews (8,9). These direct measures include measures analogous to loss days, asking about the number of days in which activities were impaired (cutback days).…”
mentioning
confidence: 99%
“…(Marque Sim ou Não, se for Não, pule para a questão 6) As próximas questões se referem aos últimos sete dias, não incluindo o dia de hoje 2) Durante os últimos sete dias, quantas horas você deixou de trabalhar por causa dos seus problemas de saúde? Inclua as horas não trabalhadas quando você esteve doente, chegou atrasado, saiu mais cedo etc., por causa de sua saúde ou problemas digestivos.…”
Section: )Você Está Atualmente Empregado (Trabalho Remunerado)?unclassified
“…[4][5][6] Most of the time, these instruments relate to individuals who are working on a formal basis or receiving regular pay and they do not include vo luntary work or housework, although most authors highlight the importance of such measurements. 7 Moreover, from researchers working on this issue, there is a generalized need for validated measurement tools for work productivity and techniques to translate these measurements into costs.…”
Section: Introductionmentioning
confidence: 99%